2007
DOI: 10.1177/0733464807299354
|View full text |Cite
|
Sign up to set email alerts
|

Healthy IDEAS

Abstract: This study evaluated an evidence-based intervention for depression delivered by case managers in three community-based service agencies to high-risk, diverse older adults. Case managers were trained to provide screening and assessment, education, referral and linkage, and behavioral activation. Outcomes addressed depression, general health status, social and physical activation, and mental health services use at baseline and 6 months. Participants (n = 94) were predominantly women (79%) and Hispanic (44%), wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Acierno et al (2012) showed that individuals with varied levels of training and expertise (ranging from recent graduates of bachelor programs in psychology to experienced social workers) were able to implement behavioral activation. Moreover, behavioral activation interventions delivered via telephone Quijano et al, 2007) or videoconferencing (Lazzari et al, 2011) were also effective. These findings suggest considerable simplicity and flexibility in implementation, which has important implications for future research and practice.…”
Section: Participant and Setting Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Acierno et al (2012) showed that individuals with varied levels of training and expertise (ranging from recent graduates of bachelor programs in psychology to experienced social workers) were able to implement behavioral activation. Moreover, behavioral activation interventions delivered via telephone Quijano et al, 2007) or videoconferencing (Lazzari et al, 2011) were also effective. These findings suggest considerable simplicity and flexibility in implementation, which has important implications for future research and practice.…”
Section: Participant and Setting Characteristicsmentioning
confidence: 99%
“…They presented with major or minor depression, and comorbid anxiety was assessed in five studies (Acierno et al, 2012;Dozeman et al, 2011;Meeks et al, 2006;Thompson et al, 1987;Turner & Leach, 2009). Few studies included older adults with cognitive impairment (Snarski et al, 2011;Teri et al, 1997), chronic medical illness (Dozeman et al, 2011;Meeks et al, 2008;Quijano et al, 2007), chronic pain Meeks et al, 2006;Quijano et al, 2007), or diagnoses of psychiatric disorders such as schizophrenia (Snarski et al, 2011); thus, there is limited evidence for the effectiveness of behavioral activation with such individuals. Conclusions are also limited for individuals of more advanced age (85 years and older) and older adults with severe depression.…”
Section: Participant and Setting Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations